Cât de săraci sunt românii: abordări subiective şi consensuale - Voicu, Bogdan (Calitatea Vieții, 2006)
Subjective and consensual poverty have a long history of debates over their meanings and measuring. In this paper I try to contribute to the debate with some data collected in Romania, between 1990 and 2005. After re-viewing the bulk of literature, I start presenting the data, mainly in longitudinal perspective, but also, where information is available, in comparative, pan-European streams. I argue that both at individual and aggregate (country) level there is a close connection between “objective” measures of richness/welfare/poverty and the subjective and consensual ones. I also argue, in the end, using Romanian case, that the various subjective measures are explained by two interrelated “satisfactions”: the one with the accumulated wealth and the one with the current accumulation. Basically, I suggest, the various measures of subjective and consensual individual wealth may be interchanged, depending on their availability within the databases.